2018
DOI: 10.1007/s11042-018-6593-1
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic usability evaluation on games: a modular approach

Abstract: Heuristic evaluation is the preferred method to assess usability in games when experts conduct this evaluation. Many heuristics guidelines have been proposed attending to specificities of games but they only focus on specific subsets of games or platforms. In fact, to date the most used guideline to evaluate games usability is still Nielsen's proposal, which is focused on generic software. As a result, most evaluations do not cover important aspects in games such as mobility, multiplayer interactions, enjoyabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In recent years, several review studies have been conducted on usability evaluation methods (Davis et al, 2020;Li et al, 2019;Rauf et al, 2019;Vargas Caceres et al, 2018;Wronikowska et al, 2021). Recently, some of these expert-based techniques have proposed new models of evaluation factors (Lee and Lee, 2019;Veral and Macias, 2019), some extended methods include new heuristics (Othman et al, 2018;Yanez-Gomez et al, 2019). Some have evaluated usability in a new generation of software engineering (Memedi et al, 2018;Rahmat et al, 2018), and others have integrated expert-based techniques and used machine learning techniques to predict several usability factors based on expert opinion (Imel et al, 2019;Ponce et al, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, several review studies have been conducted on usability evaluation methods (Davis et al, 2020;Li et al, 2019;Rauf et al, 2019;Vargas Caceres et al, 2018;Wronikowska et al, 2021). Recently, some of these expert-based techniques have proposed new models of evaluation factors (Lee and Lee, 2019;Veral and Macias, 2019), some extended methods include new heuristics (Othman et al, 2018;Yanez-Gomez et al, 2019). Some have evaluated usability in a new generation of software engineering (Memedi et al, 2018;Rahmat et al, 2018), and others have integrated expert-based techniques and used machine learning techniques to predict several usability factors based on expert opinion (Imel et al, 2019;Ponce et al, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…e heuristic evaluation method, conducted by experts, is one of the preferred methods for assessing the usability of games. Most of the modular heuristic evaluations are conducted using Neilson's proposals that focus on software [6,7]. Recent research by [8], in which a systematic review on heuristics was conducted, have reported that the heuristics and usability of educational games still offer potential for exploration in specific evaluation and validation of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Som e of the m ost com m on expert -based u sability assessm ent m ethod s inclu d e review ing gu id es based on interaction d esign gu id elines, innovative assessm ent, cognitive e nhancem ents, u sage paths, form al u sability inspections, and innovative m arches [15]. Recently, these experts-based techniqu es have becom e extend ed throu gh proposing new m od els of evalu ation fa ctors [16]; [17], new heu ristics [18]; [19], u sability evalu ation in a new generation of softw are [20]; [21], integration of expert-based techniqu es and u sing m achine learning techniqu es to pred ictive several u sability factors based on expert' opinion [22]; [55]. As w e d iscu ssed , the expert-based u sability evalu ation in the literatu re is com pletely static.…”
Section: Introductionmentioning
confidence: 99%